Kindergarten Resource Pack Communication, Language and Literacy - Term I - The City School (Lahore : The City School)
It helps them learn to recognize, trace, and write basic letters and simple words. Fun activities like matching, rhymes, and oral practice build vocabulary and listening skills. The book supports early reading and writing through playful, interactive learning.
Location: 1B
Keywords: Textbook